Technology, commercialization and gender : a global perspective - Wynarczyk, Pooran, 1951-; Ranga, Marina (Palgrave Macmillan, 2017)
This timely collection seeks to advance our understanding of the role of women in technology commercialization. Widely acknowledged as the fundamental components of economic prosperity and global competitiveness, current literature on the management of technological change focuses on processes and institutions and neglects to address gender dimensions. Responding to this pressing need to critically examine women?s participation and contribution, 'Technology, Commercialization and Gender' addresses the construction of gendered identities within predominantly male-dominated work environments such as technology transfer, patenting, licensing and management of Intellectual Property Rights and R & D. With contributions from globally renowned scholars this important book aims to broaden the current understanding of the dynamics and implications of this phenomenon and as such, seeks to address gaps in knowledge at an international level.